Jaboticaba (Myrciaria jaboticaba) Attenuates Ventricular Remodeling after Myocardial Infarction in Rats - Renata Candido da Silva; Bertha Furlan Polegato; Paula Shmidt Azevedo; Ana Angélica Fernandes; Katashi Okoshi; Sergio Alberto Rupp de Paiva; Marcos Ferreira Minicucci; Leonardo Antônio Mamede Zornoff (Antioxidants, 2022)
The cardiac remodeling after myocardial infarction is characterized by inflammation and oxidative stress. Thus, this study aimed to test the hypothesis that jaboticaba, due to its anti-inflammatory and antioxidants properties, attenuates cardiac remodeling after myocardial infarction. Wistar rats were submitted to myocardial infarction due to coronary artery occlusion, and divided into four experimental groups: C, sham control animals; I, animals submitted to myocardial infarction, received a standard diet; IJ2, animals submitted to myocardial infarction, received a standard diet plus 2% jaboticaba; and IJ4, animals submitted to myocardial infarction, received a standard diet plus 4% jaboticaba. After a three-month follow-up, echocardiography, histology, oxidative stress, and cardiac energy metabolism were analyzed. There was no difference in infarct size or mortality among the infarcted groups. The IJ4 group displayed improved diastolic function, as assessed by isovolumetric relaxation time normalized to the heart rate. As expected, the percentage of collagen was higher in all infarcted groups than in the C group. However, the IJ2 group had less collagen than groups I and IJ4. The IJ4 group presented lower PFK activity than I and IJ2, and lower pyruvate dehydrogenase activity than controls, whereas the IJ2 group showed no differences compared to the control group in both LDH and ATP synthase activity. The 2% and 4% doses attenuated lipid peroxidation and increased the activity of glutathione peroxidase compared with the I group. In conclusion, jaboticaba attenuated the remodeling process after myocardial infarction, which was associated with decreased oxidative stress and improved energy metabolism.